Collapse of Pre-COVID-19 Differences in Performance in Online vs. In-Person College Science Classes, and Continued Decline in Student Learning - Gregg R. Davidson; Hong Xiao; Kristin Davidson (MDPI AG, 2024)
Studies comparing student outcomes for online vs. in-person classes have reported mixed results, though with a majority finding that lower-performing students, on average, fare worse in online classes, attributed to the lack of built-in structure provided by in-person instruction. The online/in-person outcome disparity was normative for non-major geology classes at the University of Mississippi prior to COVID-19, but the difference disappeared in the years after 2020. Previously distinct trendlines of GPA-based predictions of earned-grade for online and in-person classes merged. Of particular concern, outcomes for in-person classes declined to match pre-COVID-19 online expectations, with lower-GPA students disproportionally impacted. Objective evidence of continued decline in student learning, masked by sliding grading scales, is also presented with a long-term record of exam scores drawing from the same question pool for over a decade. Average scores remained relatively constant until COVID-19. Scores then declined in each successive year, attributed to an increase over time in the percentage of enrolled students who had been in high school during the pandemic shutdowns. At the close of 2023, exam scores showed no signs of returning to pre-COVID-19 outcomes. The negative impacts of the shutdowns, with greater impact on those who were in high school during the pandemic, appear to be due to a loss in the developmental life-skills (e.g., self-motivation, focus, critical thinking, social development) needed to thrive in college, not just reduced exposure to preparatory subject material. These results provide a global cautionary message for the management of future pandemics.